2018
DOI: 10.1007/s00330-017-5237-6
|View full text |Cite
|
Sign up to set email alerts
|

To evaluate the feasibility of magnetic resonance imaging in predicting unusual site ectopic pregnancy: a retrospective cohort study

Abstract: • MRI is being increasingly used as a problem-solving modality in ectopic pregnancy. • MRI plays an important role in early diagnosis of unusual ectopic pregnancy. • Knowledge of MRI features in EP is essential to determinate appropriate management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…The ultrasound diagnosis enables precise measurement of the physiological tissue structure and morphology in patients, with the diagnostic value that has been proven in diseases including adenomyosis and primary fallopian tube cancer [ 15 ]. The thickness of the muscle layer in the lower segment of the anterior uterine wall is currently a common index for the clinical diagnosis of CSP, which can fully reflect the damage situation at the uterine scar [ 16 ]. The TVA and TAS are two common modalities of ultrasound diagnosis to provide effective and important information for the treatment and prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasound diagnosis enables precise measurement of the physiological tissue structure and morphology in patients, with the diagnostic value that has been proven in diseases including adenomyosis and primary fallopian tube cancer [ 15 ]. The thickness of the muscle layer in the lower segment of the anterior uterine wall is currently a common index for the clinical diagnosis of CSP, which can fully reflect the damage situation at the uterine scar [ 16 ]. The TVA and TAS are two common modalities of ultrasound diagnosis to provide effective and important information for the treatment and prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that diffusion-and fat saturation T1-weighted images were the most accurate for the detection of EPs, picking up 100.0% and 93.3% of the 15 cases, respectively. 27 As such, the authors concluded that the use of MRI for the early diagnosis of early EPs should be considered, following negative US findings in some highly suspicious cases. 27…”
Section: Diagnostic Techniquesmentioning
confidence: 99%
“…27 As such, the authors concluded that the use of MRI for the early diagnosis of early EPs should be considered, following negative US findings in some highly suspicious cases. 27…”
Section: Diagnostic Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI can be a useful problem‐solving tool in patients who have an inconclusive or confounding ultrasound, particularly when there are factors affecting the ultrasound image quality, such as severe tenderness, large body habitus, excessive bowel gas, and the coexistence of ovarian mass . MRI is highly accurate in identifying the location of an extrauterine gestational sac, as it can localize the gestational sac in 93–100% of patients with an inconclusive ultrasound . Localization of the sac can help to guide management decisions in both surgical candidates and candidates for conservative treatment …”
Section: Acute Gynecologic Conditions Related To Pregnancymentioning
confidence: 99%